(The reality of agricultural crop development in Iraq) (Journal of the College of Basic Education, 2022)
The agricultural sector is gaining importance from the importance and vitality of the sector in which it operates. This sector, which is the primary field of production and the main source of capital accumulation and the liberation of the labor force necessary for the development of other economic sectors, is at the same time the main source for the extension of national industries, which requires a mechanism of raw materials, Its products are therefore considered the necessary agricultural development for comprehensive development It is based on the problem that Iraq is a country rich in its potential and resources. It has become a food importing country to meet its needs of essential commodities and no longer meets the requirements of local need. Therefore, the research hypothesis adopts contemporary concepts of agrarian reform and the reconstruction of productive relations.The research concluded that there are significant differences between governorates in agricultural production. According to the possibility of each province and the conditions allowed by natural and human conditions. And that there is a negative trend in agricultural production due to rising costs of fuel and energy used in agricultural production and high costs of tillage, harvesting and maintenance and the entry of imported goods into Iraq.The study, especially the spatial data, was supported by maps and was mostly used in drawing according to the logarithmic analysis technique, which was proportional to the distribution of data for this research. The research chose this method of drawing among the best of the other methods. These maps were introduced into the computer in GIS technology, Modern drawing depends on the latitude and longitude